2011
DOI: 10.1103/physrevlett.106.175503
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Integer Automaton behind Crystal Plasticity

Abstract: Power law fluctuations and scale free spatial patterns are known to characterize steady state plastic flow in crystalline materials. In this Letter we study the emergence of correlations in a simple Frenkel-Kontorova (FK) type model of 2D plasticity which is largely free of arbitrariness, amenable to analytical study and is capable of generating critical exponents matching experiments. Our main observation concerns the possibility to reduce continuum plasticity to an integer valued automaton revealing inherent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 62 publications
2
56
1
Order By: Relevance
“…This identification, which we checked to be respected by the dislocation density fluctuations in the microscopic model [7], allows one to interpret observed behaviors in terms of the values of the parameters a, c, D…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…This identification, which we checked to be respected by the dislocation density fluctuations in the microscopic model [7], allows one to interpret observed behaviors in terms of the values of the parameters a, c, D…”
mentioning
confidence: 62%
“…A different point of view emerged from the analysis of high resolution acoustic emission (AE) data in plastically deforming HCP crystals which showed that temporal fluctuations may be power-law distributed in size and energy [2] and may be clustered in both space [3] and time [4]. These observations, suggesting that averages do not represent typical behavior, were corroborated by the study of statistics of slip events in microand nano-pillars [5,6] for FCC and BCC metals and supported by numerical models [2,7,10,12].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…However, our results suggest that this simple picture is incomplete, calling for novel theoretical ideas to properly describe the glassy, critical-like dynamics observed in the jammed phase of the system. Dislocation physics has been recently studied with many simplified models from discrete dislocation dynamics [17][18][19] to phase field [20] and automaton models [21]. Here, we consider the stress-controlled hysteretic dynamics within a two-dimensional discrete dislocations dynamics model [17].…”
mentioning
confidence: 99%
“…45,[48][49][50][51]53 These systems evolve toward a critical state represented by the ensemble of metastable states through which the system passes via an avalanche-like dynamics whose amplitudes and durations follow power laws (see Ref. 52 for a review).…”
Section: Irreversibility and Intermittent Dynamicsmentioning
confidence: 99%